Dental fluorosis and its influence on children's life - Suzely Adas Saliba MOIMAZ; Orlando SALIBA; Lívia Bino MARQUES; Cléa Adas Saliba GARBIN; Nemre Adas SALIBA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This study verified the prevalence of dental fluorosis in 12-year-old children and its association with different fluoride levels in the public water supply, and evaluated the level of perception of dental fluorosis by the studied children. To assess fluorosis prevalence, clinical examinations were performed and a structured instrument was used to evaluate the self-perception of fluorosis. The water supply source in the children's area of residence since birth was used as the study criterion. In total, 496 children were included in the study. Fluorosis was diagnosed in 292 (58.9%) children; from these, 220 (44.4%) children were diagnosed with very mild fluorosis, 59 (11.9%) with mild fluorosis, 12 (2.4%) with moderate fluorosis, and 1 (0.2%) child with severe fluorosis. A significant association (p = 0.0004) was observed between the presence of fluorosis and areas with excessive fluoride in the water supply. Among the 292 children that showed fluorosis, 40% perceived the presence of spots in their teeth. The prevalence of fluorosis was slightly high, and the mildest levels were the most frequently observed. Although most of the children showed fluorosis to various degrees, the majority did not perceive these spots, suggesting that this alteration did not affect their quality of life.